ANALISIS NILAI TAMBAH UBI KAYU DAN USAHA KERIPIK SINGKONG INDUSTRI RUMAH TANGGA DI DESA TANAH MAS KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Indrawani sinoem; Ursula Damayanti (JURNAL TRIAGRO, 2018)
Analysis of added value of cassava and cassava chip business in home industry in Tanamas Village, Talang Kelapa District, Banyuasin District. The purpose of this study was to determine the added value and profits of cassava as raw material for cassava chips produced Household Industry in Tanahmas Village, Talang Kelapa District, Banyuasin District.  This research is a case study with a case object is the home industry in Tanahmas Village, Talang Kelapa District. The data processing method used in this study was the Hayami method to analyze the added value of cassava and profit analysis, and the R / C to analyze the business of cassava chips in the home industryin Tanahmas Village, Talang Kelapa District, Banyasin District. The results were obtained, the added value of cassava in Ibu Rama's Home Industry in fifteen times the production process per month, was Rp. 9,622 per kg, while the analysis of the business of home industry of Mrs. Rama obtained a business profit of Rp. R / C as fast as 2.28.